Relationship of the Fusion Stage of Spheno-Occipital Synchondrosis with Midpalatal and Zygomaticomaxillary Sutures on Cone-Beam Computed Tomography Scans of Patients Aged Between 7 and 21 Years - Niloufar Tashayyodi; Zahra Dalili Kajan; Farzane Ostovarrad; Negar Khosravifard (Galenos Yayinevi, 2023)
Objective:This study assessed the relationship of the fusion stage of spheno-occipital synchondrosis (SOS) with midpalatal (MPS) and zygomaticomaxillary (ZMS) sutures on cone-beam computed tomography (CBCT) scans of 7 to 21-year-old patients.Methods:This cross-sectional study evaluated the CBCT scans of 176 patients between 7 and 21 years presenting to a maxillofacial radiology clinic. The fusion stage of SOS was determined using a five-stage classification system. The percentage of opening depth of MPS was measured on two middle coronal cuts in the anterior and posterior half of the palate. To assess ZMS, suture fusion was evaluated in four age groups in the axial cut visualizing its maximum length. Data were analyzed using the Kruskal-Wallis, Mann- Whitney U, and Bonferroni tests and regression models.Results:The percentage of MPS opening significantly decreased in both the anterior and posterior halves with age (p<0.002). With an increase in SOS grade, the percentage of MPS opening in both the anterior and posterior halves significantly decreased (p<0.001). By an increase in the ZMS stage, the SOS grade significantly increased (r=0.565, p<0.001).Conclusion:The MPS opening percentage in the anterior and posterior halves decreased with age, with a greater reduction in the posterior half. A significant inverse correlation exists between the SOS fusion stage and the percentage of MPS opening. In SOS grades I-III, the mean percentage of MPS opening was 100% in all age groups (with the highest frequency of ZMS stage I), indicating a higher chance of success for orthodontic treatments such as rapid maxillary expansion in these individuals.